Electron mobility in CdxHg₁₋xSe - Malyk, O.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Electron scattering on the short-range potential caused by interaction with
polar and nonpolar optical phonons, piezoelectric and acoustic phonons, static strain,
ionized impurities in CdxHg₁₋xSe (0 ⩽ x ⩽ 0.547) samples annealled in selenium vapour or
in dynamic vacuum are considered. Within the framework of the precise solution of the
stationary Boltzmann equation on the base of short-range principle, temperature
dependences of the electron mobility within the range 4.2 – 300 K are calculated. A good
coordination of the theory to experiment in the investigated temperature range is
established.